Peptic ulcer and intestinal metaplasia associated with Helicobacter pylori colonization in gastric heterotopia of the tongue - Ufuk Berber,; İsmail Yılmaz,; Bülent Evren Erkul,; Mustafa Kaplan, (Turkish Journal of Gastroenterology, 2019)
-